2013
DOI: 10.1159/000348435
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differentiation in an All-Female (XX) Rainbow Trout Population with a Genetically Governed Masculinization Phenotype

Abstract: Sex determination is known to be male heterogametic in the rainbow trout, Oncorhynchus mykiss; however, scattered observations that deviate from this rather strict genetic control have been reported. Here, we provide a detailed morphological and histological characterization of the gonadal differentiation and development (from 43 days postfertilization to 11 months of age) in an all-female (XX) population with a genetically governed masculinization phenotype. In comparison with control males and females, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
4
7
0
Order By: Relevance
“…In agreement with previous studies performed with mal -carrying animals [20] [22] , we confirmed that the masculinization rates at the reference temperature of 12°C were variable among half-sib progeny (experiment A) and independent progeny (experiment B) depending on the breeding pair, respectively. This result was clearly demonstrated in our common garden experiment, controlled for possible tank effects, in which different progeny exhibited different masculinization rates independent from the temperature effects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies performed with mal -carrying animals [20] [22] , we confirmed that the masculinization rates at the reference temperature of 12°C were variable among half-sib progeny (experiment A) and independent progeny (experiment B) depending on the breeding pair, respectively. This result was clearly demonstrated in our common garden experiment, controlled for possible tank effects, in which different progeny exhibited different masculinization rates independent from the temperature effects.…”
Section: Discussionsupporting
confidence: 92%
“…Despite a strict male heterogamety in rainbow trout, spontaneous masculinization has been found in some XX fish belonging to a population of gynogenetic doubled haploid individuals [20] . Analysis of the transmission of this male phenotype in a three generation pedigree supported the hypothesis that a recessive mutation in one putative minor sex determination factor (termed mal ), together with other sex modifier loci, was responsible for the partial or full masculinization of some of these XX individuals [20] [22] . Preliminary observations also suggested that this expression of maleness was influenced by environmental factors; low temperature during the first stages of development reduced the frequency of masculinized individuals [Quillet et al, unpublished data].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Within those intersex individuals, whatever the rearing temperature of fry, the right gonad was very often more masculinised than the left gonad. This particularity was first described by Quillet et al (2004) 40 and confirmed by Valdivia et al (2013Valdivia et al ( , 2014 12,15 , in families originating from the INRA XXmal carrying line. Under normal rearing condition, the left-right asymmetry (LR) is almost undetectable as intersex fish remain rare and poorly described.…”
Section: Discussionmentioning
confidence: 63%
“…However, despite a strict sex-linkage of the sdY locus in many salmonid species 8 , spontaneous masculinisation of XX females have been reported in rainbow trout, first in experimental groups 11 , but also in commercial populations (unpublished data). These spontaneous masculinisation and their transmission across generations have been characterized in gynogenetic families, where the role of minor genetic factors acting in addition to the major sdY sex determination system has been suspected 11,12 . Later, Guyomard et al 13 (2014) detected QTLs associated to masculinisation in two doubled haploid gynogenetic trout families.…”
Section: Introductionmentioning
confidence: 99%